PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN PERSEPSI INOVASI SEBAGAI VARIABEL INTERVENING (Studi Pada Pemerintah Kota Pekanbaru) - Wanda Dedi Saputra; Desmiyawati '; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Managerial performance is one of the factors that can be used to increase the effectiveness of the organization. In order that these objectives can be achieved effectively it is necessari to pay attention to the participation in the preparation of the budget as well as the existence of a perception of innovation in the relationship decisions related to budget. This study aimed to investigate the effect of budget participation on managerial performance in public sector organizations. The study also examined whether the perception of innovation mediates the effect of budget participation on managerial performance.This research data collection using questionnaire survey. The questionnaire submitted to 78 structural officials SKPD Pekanbaru, 66 questionnaires were returned and 57 questionnaires (73.08%) complete and can be processed. The data collected were processed using SPSS 17.0 with path analysis to examine the effect of direct and indirect budget participation on managerial performance with a significance level of 0.05 or 5%.The results of this study indicate that the direct effect of budget participation on managerial performance. Participation budget also significantly influence the perception of innovation. However, the budget does not affect the participation of indirect managerial performance through an intervening variable perception of innovation.Keywords : budgetary participation, managerial performance, perception of Innovation, and publik sector organization